2016
DOI: 10.1007/s11356-016-6758-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients removal and nitrous oxide emission during simultaneous nitrification, denitrification, and phosphorus removal process: effect of iron

Abstract: The short- and long-term influences of ferric iron (Fe(III)) on nutrients removal and nitrous oxide (N2O) emission during SNDPR process were evaluated. According to the continuous cycle experiments, it was concluded that the addition of Fe(III) could lower the nitrogen removal of the following cycle during SNDPR process, which was mainly induced by the chemical removal of phosphorus. However, the impacts were transitory, and simultaneous nitrogen and phosphorus removal would recover from the inhibition of Fe(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The NH 3 removal occurs theoretically via three mechanisms: gaseous NH 3 stripping to the atmosphere, NH 3 assimilation in microbe biomass, and biological nitrification. From the results, it can be noticed that there is limited fluctuation in nitrate concentration, as recorded in Figure 5 in the final effluent; this indicates that nitrification has limited presentation [33]. The nitrification process is accomplished by two groups of nitrifying bacteria Nitrosomonas and Nitrobacter [33].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The NH 3 removal occurs theoretically via three mechanisms: gaseous NH 3 stripping to the atmosphere, NH 3 assimilation in microbe biomass, and biological nitrification. From the results, it can be noticed that there is limited fluctuation in nitrate concentration, as recorded in Figure 5 in the final effluent; this indicates that nitrification has limited presentation [33]. The nitrification process is accomplished by two groups of nitrifying bacteria Nitrosomonas and Nitrobacter [33].…”
Section: Resultsmentioning
confidence: 90%
“…From the results, it can be noticed that there is limited fluctuation in nitrate concentration, as recorded in Figure 5 in the final effluent; this indicates that nitrification has limited presentation [33]. The nitrification process is accomplished by two groups of nitrifying bacteria Nitrosomonas and Nitrobacter [33].…”
Section: Resultsmentioning
confidence: 90%
“…It is noticed that the e uent TP concentration was signi cantly higher when P removal agent was added compared to the scenarios without their addition, indicating the negative effect of these agents on e uent NH 3 -N concentration (Fig. 3 (g)) (Jia et al 2016). Meanwhile, the concentration of e uent TP exceeded the standard considerably, when the P removal agent was not enhanced at the same multiple as the treated quantity.…”
Section: Predicted Hyper-quantity Functional Performance Of the Processmentioning
confidence: 94%
“… Wang et al (2014) have examined the effect of Fe 3+ on nitrogen (N) removal performance in a modified biological aerated filter, showing that nitrification performance was enhanced in the presence of Fe 3+ , whereas denitrification performance was inhibited. Furthermore, Jia et al (2016) have demonstrated that the use of acetate as a carbon source in a laboratory-scale sequencing batch reactor contributed to promoting total nitrogen (TN) removal at an Fe 3+ concentration of 40 mg/L. In contrast, in a batch reactor with citrate as the carbon source, 17.7 mg/L Fe 3+ was found to suppress the overall denitrification process ( Ramírez et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%